Ectopic activation of germline and placental genes identifies aggressive metastasis-prone lung cancers - Rousseaux, Sophie; Debernardi, Alexandra; Jacquiau, Baptiste; Vitte, Anne-Laure; Vesin, Aurélien; Nagy-Mignotte, Hélène; Moro-Sibilot, Denis; Brichon, Pierre-Yves; Lantuejoul, Sylvie; Hainaut, Pierre; Laffaire, Julien; de Reyniès, Aurélien; et al. (Science translational medicine, 2013)
Activation of normally silent tissue-specific genes and the resulting cell "identity crisis" are the unexplored consequences of malignant epigenetic reprogramming. We designed a strategy for investigating this reprogramming, which consisted of identifying a large number of tissue-restricted genes that are epigenetically silenced in normal somatic cells and then detecting their expression in cancer. This approach led to the demonstration that large-scale "off-context" gene activations systematically occur in a variety of cancer types. In our series of 293 lung tumors, we identified an ectopic gene expression signature associated with a subset of highly aggressive tumors, which predicted poor prognosis independently of the TNM (tumor size, node positivity, and metastasis) stage or histological subtype. The ability to isolate these tumors allowed us to reveal their common molecular features characterized by the acquisition of embryonic stem cell/germ cell gene expression profiles and the down-regulation of immune response genes. The methodical recognition of ectopic gene activations in cancer cells could serve as a basis for gene signature-guided tumor stratification, as well as for the discovery of oncogenic mechanisms, and expand the understanding of the biology of very aggressive tumors.